PENERAPAN METODE PEMBELAJARAN CIRC TERHADAP MENULIS TEKS CERAMAH PADA SISWA SMA - Wida Nengsih; Nur Atikah; Alfa Mitri Suhara (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The matter of this study is the problem of students who find it difficult when writing lecture texts, this can be seen from the results of repeated tests of students who did not meet the achievement targets of the success of evaluation. The researcher formulated this research problem in improving students' ability in writing pre-text lectures and after applying the CIRC method. The purpose of this study is to improve student learning outcomes in learning to write lecture texts. This research is in the form of one group pretest-posttest research, and the subject is class XI students totaling 44 students. The techniques applied are test and observation techniques. After all, data has been collected, researchers carry out data processing by analyzing data in the form of the results of all student work. Based on these results, the researcher can conclude that the test results have increased the value of students pre and post using the learning method. From the results of the pretest, the students' scores were 73.8. While the posttest value of students is 83.6. This refers to the hypothesis made if the teacher uses the CIRC learning method, the ability of students to write lecture texts will increase.